2014
DOI: 10.1038/srep06469
|View full text |Cite
|
Sign up to set email alerts
|

Research of dose-effect relationship parameters of percutaneous microwave ablation for uterine leiomyomas - a quantitative study

Abstract: Eighty eight patients with 91 uterine leiomyomas who underwent ultrasound-guided percutaneous microwave ablation (PMWA) treatment were prospectively included in the study in order to study the dose-effect relationship parameters (DERP) of PMWA for uterine leiomyomas and its relationship with T2-weighted MR imaging (T2WI). Based on the signal intensity of T2WI, uterine leiomyomas were classified as hypointense, isointense, and hyperintense. During ablation, leiomyomas were treated with quantitative microwave ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…US-guided percutaneous microwave ablation (PMWA) therapy utilises electromagnetic microwave heat to induce cellular death via coagulation necrosis. Single-centre research studies have confirmed the safety and efficacy of this treatment; it has been shown that this treatment is effective, minimally invasive and uterus-conserving with effective relief of clinical symptoms after therapy [4][5][6][7][8][9][10][11]. However, no multicentre study with a large sample has been conducted to confirm the conclusions of these single-centre investigations.…”
Section: Introductionmentioning
confidence: 99%
“…US-guided percutaneous microwave ablation (PMWA) therapy utilises electromagnetic microwave heat to induce cellular death via coagulation necrosis. Single-centre research studies have confirmed the safety and efficacy of this treatment; it has been shown that this treatment is effective, minimally invasive and uterus-conserving with effective relief of clinical symptoms after therapy [4][5][6][7][8][9][10][11]. However, no multicentre study with a large sample has been conducted to confirm the conclusions of these single-centre investigations.…”
Section: Introductionmentioning
confidence: 99%
“…The mean fibroid volume reduction following this treatment is between 90 and 94%, and there have been no major adverse events described [41,42]. The effectiveness of microwave ablation of uterine fibroids in terms of the thermal dose effect is related to the appearance of fibroids on T2-weighted MRI [43]. When viewing uterine fibroids on T2-weighted MRI, these tumours can be described as being higher in signal intensity, equal to, or less high in signal intensity when compared with skeletal muscle; these fibroids are referred to as hyperintense, isointense or hypointense respectively.…”
Section: Microwave Ablation Of Uterine Fibroidsmentioning
confidence: 90%
“…Hypointense and isointense fibroids have a higher fibre content and lower cellular content, and a reduced blood supply compared with fibroids of hyperintense appearance [44]. A study of the thermal dose-related effectiveness of percutaneous microwave ablation found that the volumes of ablation achieved for a given microwave power were reduced in hyperintense fibroids compared with hypointense or isointense fibroids [43].…”
Section: Microwave Ablation Of Uterine Fibroidsmentioning
confidence: 99%
“…MWA has gained increasing attention because of its high thermal efficiency. Moreover, ultrasound-guided percutaneous microwave ablation (PMWA) for adenomyosis can relieve symptoms of adenomyosis and reduce uterine volume [12,16,17], and it does not affect ovary function [11,12,18]. However, PMWA has the potential risk of collateral thermal damage to the nearby intestinal tract, and a percutaneous approach is technically challenging because of bowel interference.…”
Section: Introductionmentioning
confidence: 99%